Dualisme Akad Ijarah Dan Ijarah Muntahiyah Bit-Tamlik (IMBT) Perspektif Fiqh Muamalah - Sisminawati Sisminawati; Ahmad Suminto (Musyarakah: Journal of Sharia Economic (MJSE), 2021)
he reality of practice in the field regarding ijarah financing contracts and ijarah vomitiyah bit-Tamlik differs from the basic theory, namely fiqh muamalah. So this article tries to recite or dialogue fiqh muamalah theory about the concept of lease with the reality of applications that occur in Islamic financial institutions. In this study, the author calls the dualism of the ijarah contract and the Ijarah Muntahiyah Bit-Tamlik (IMBT) fiqh muamalah perspective. The writing method in this study is a combination of two writing methods (mix method), namely library research and field studies (file research), with a descriptive-analytic qualitative approach. The literature study is carried out by collecting data on the thoughts and opinions of experts (experts) in several books in the library. Meanwhile, field studies are carried out through interviews and observations in Islamic financial institutions, as related objects. The results of this study indicate that ijarah Muntiyah bit-Tamlik (IMBT) is a kind of combination between a sale and purchase contract and a lease or more precisely a lease agreement which ends with the ownership of the goods in the hands of the lessee. In the IMBT contract there is a lease-purchase contract, there have been two transactions or contracts in one transaction. Because in practice payments made during the installment period can change function. If the buyer cannot pay off the installments, then the payment functions as a rent but if he is able to pay it off, it serves as a sale and purchase price.